Linhagem materna: Qual a sua influência em características pré e pós desmama em bovinos da raça Nelore? - Quintino, H. P.; Ferraz, J. B S; Eler, J. P.; Balieiro, J. C C; Mourão, G. B.; Mattos, E. C.; Figueiredo, L. G G [UNESP] (My University, 2009)
The present work had as objective to evaluate the effects of the introduction of the maternal lineage (Lc), representing the mitochondrial inheritance, in the model of genetic evaluation on birth weight (BW), weight for 120 days (W120), weaning weight (WW), weight at 12 month (W12), weight at 18 month (W18), weight gain from weaning to 18 month (WG18), scrotal perimeter (SP) and temperament (TEMP) of a Brazilian Nelore herd. Two models had been used for raise a comparison among of estimates the (co)variances components and genetic parameter, been the first equal one to currently used in the genetic evaluations of this herd, and second included the random effect of maternal lineage. Amongst the analyzed characteristics, the maternal lineage effect was significant (P<0.05) for W18 and SP only it, where this effect was responsible for 3% and 7%, respectively, of phenotypic variance could be explained by Lc effect. For besides characteristics, however not significant, this effect was responsible for 1% and 9% of phenotypic variance.
Maternal lineage: What is its influence on characteristics pre and post weaning in the Nellore cattle
Keywords: Beef cattle; Cytoplasm effects; Mitochondrial inheritance; Weaning weight; Bos